SISTEM PENDUKUNG KELAYAKAN PEMBERIAN KREDIT ULTRA MIKRO DENGAN METODE PERBANDINGAN EKSPONENSIAL. - Wiliani, Ninuk; Adi Saputra, Mulyana (Innotech: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2024)
The process of providing credit is now can be done easily through the presence of BRILink agents with additional facilities besides payment points namely as partners of ultra micro loans which are now popularly known as UMi Partners, which is BRILink agents can distribute micro loans with a loan range of 1 up to 5 million. The study used the Exponential Comparison Method (MPE) to determine lending decisions in order to optimize all existing information systems with the implementation of systems that can be used and applied by UMi partners to improve the process of granting creditworthiness to partners. The system used the NetBeans IDE with Java programming. The results of the calculations were precisely calculated by the system according to the manual calculations that have been carried out so that the results can be applied properly so as to produce creditworthiness which helps the loan granting process.